2017
DOI: 10.1021/acs.jpca.7b05830
|View full text |Cite
|
Sign up to set email alerts
|

J(Si,H) Coupling Constants of Activated Si–H Bonds

Abstract: We outline in this combined experimental and theoretical NMR study that sign and magnitude of J(Si,H) coupling constants provide reliable indicators to evaluate the extent of the oxidative addition of Si-H bonds in hydrosilane complexes. In combination with experimental electron density studies and MO analyses a simple structure-property relationship emerges: positive J(Si,H) coupling constants are observed in cases where M → L π-back-donation (M = transition metal; L = hydrosilane ligand) dominates. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 86 publications
(237 reference statements)
1
18
2
Order By: Relevance
“…This methodology has been introduced recently by one of us to study the related bonding scenario of σ agostic interactions and σ silane complexes. [28a], We will show in the following that application of hydrostatic pressure can also be used to compress the η 1 (C–H)Pt moieties in single crystals of 2 to push the C–H br bond of the chloroform ligand closer to the metal. As a consequence we might systematically enhance the Pt(d z ² )→σ*(C–H) back donation and Pt(RY)←σ(C–H) σ donation to trigger the C–H bond activation upon increasing pressure similar to the electronic situation in σ‐agostic d 8 Ni complexes .…”
Section: Methodsmentioning
confidence: 99%
“…This methodology has been introduced recently by one of us to study the related bonding scenario of σ agostic interactions and σ silane complexes. [28a], We will show in the following that application of hydrostatic pressure can also be used to compress the η 1 (C–H)Pt moieties in single crystals of 2 to push the C–H br bond of the chloroform ligand closer to the metal. As a consequence we might systematically enhance the Pt(d z ² )→σ*(C–H) back donation and Pt(RY)←σ(C–H) σ donation to trigger the C–H bond activation upon increasing pressure similar to the electronic situation in σ‐agostic d 8 Ni complexes .…”
Section: Methodsmentioning
confidence: 99%
“…These nonclassical hydrosilane complexes have been the subject of a number of reviews, and from a molecular orbital perspective, they are typically described using a modification of the Dewar–Chatt–Duncanson bonding model, with concomitant σ donation and π backdonation to/from the metal (Figure ). A variety of terms have been employed to describe these intermediate complexes, , and comprehensive studies by a number of groups, including those of Nikonov, Sabo-Etienne, , and Scherer, have shown that a continuum exists between σ-hydrosilane complexes involving minimal π-backdonation, and classical silyl hydride complexes. This continuum follows the oxidative addition/reductive elimination reaction coordinate, with progressively weakening Si–H interactions being indicative of a greater degree of oxidative addition.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of nonclassical hydrosilane complexes have naturally focused on the strength of the Si–H interaction, from which the degree of oxidative addition can be inferred. These strengths have often been determined computationally, ,,,,, while experimental studies have primarily involved solid-state structural determination of the Si–H distance. However, care must be taken when discussing Si–H distances determined by X-ray crystallography, due to difficulties associated with accurately locating hydrogen atoms from the difference map.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations